The effect of 8-OH-DPAT and dapoxetine on gene expression in the brain of male rats during ejaculation - Xijun Qin; Xiaojun Ma; Dongping Tu; Zuliang Luo; Jie Huang; Changming Mo (Elsevier, 2017)
The 5-HT1A receptor agonist 8-hydroxy-2-[di-n-propylamino] tetralin (8-OH-DPAT) promotes ejaculation of male rats, whereas dapoxetine delays this process. However, the gene expression profile of the brain at ejaculation following administrationof these two compounds has not been fully elucidated. In the present study, a transcriptomic BodyMap was generated by conducting mRNA-Seq on brain samples of male Sprague-Dawley rats. The study included four groups: pre-copulatory control (CK) group, ejaculation (EJ) group, 0.5 mg/kg 8-OH-DPAT-ejaculation group (DPAT), and 60 mg/kg dapoxetine-ejaculation (DAP) group. The resulting analysis generated an average of approximately 47 million sequence reads. Significant differences in the gene expression profiles of the aforementioned groups were observed in the EJ (257 genes), DPAT (349 genes) and the DAP (207 genes) compared with the control rats. The results indicate that the expression of Drd1 and Slc6a3 was significantly different after treatment with 8-OH-DPAT, whereas the expression of Drd4 was significantly different after treatment with dapoxetine. Other genes, such as Wnt9b, Cdkn1a and Fosb, exhibited significant differences in expression after the two treatments and are related to bladder cancer, renal cell carcinoma and sexual addiction. The present study reveals the basic pattern of gene expression that was activated at ejaculation in the presence of 8-OH-DPAT or dapoxetine, providing preliminary gene expression information during rat ejaculation.